Do CO2 emissions, per capita GDP, public and private health expenditures matter for the health of older adults: empirical evidence from the E7 countries - Köroğlu, Muhammet Ali; Sart, Gamze; Bayar, Yilmaz; Danilina, Marina (Frontiers in Public Health, 2025)
BackgroundImprovements in life expectancy, along with decreases in fertility rates, have caused population aging in many countries. However, the environmental, economic, and social determinants of older adults’ health have not been sufficiently researched.MethodsThe objective of this research is to explore the effects of CO2 emissions, per capita GDP, and public and private health expenditures on the health of older adults in E7 countries during the period 2000–2021, using causality and cointegration methods.ResultsThe findings of the JKS causality test indicate a reciprocal interaction among life expectancy at age 60 (LE60), healthy life expectancy at age 60 (HALE60), CO2 emissions, per capita GDP, and public and private health expenditures. Furthermore, the findings of the long-term analysis reveal that CO2 emissions negatively impact LE60 and HALE60, whereas per capita GDP and public and private health expenditures positively influence LE60 and HALE60.ConclusionThe findings of this study highlight that the stringency of environmental policies, development of renewable energy technologies, income equality, and efficiency of health and social security systems are crucial for improving LE60 and HALE60.